Portfolios as assessment for learning: A case study of pre-service Foundation Phase teacher education students - Barends, Z.; Lebethe, A.; Jacobs, A. H. M. (South African Journal of Higher Education, 2023)
South African Foundation Phase teacher education programmes are criticised for not delivering critical and creative students who can rightfully take their place in an ever-changing world. Moreover, the demand for developing teacher education programmes that are of high quality and lead to meaningful development of teachers as well as several national and institutional teacher education policy changes has led to revisions to approaches to assessment. The aim of this article is to indicate how portfolios can be used as a reflective learning tool in assessment. A qualitative exploratory case study is presented where Foundation Phase teacher education portfolios were analysed thematically to establish whether portfolios promote learning through students’ engagement in reflection. We argue that student reflections through portfolios have the potential of enhancing the process of thinking about learning, thereby encouraging students to think about more than just their marks, but also their personal development and growth. An analysis of the data showed that students developed the ability to reflect as they progressed through the portfolio, albeit superficially. There were strong indicators that the portfolio tasks enabled different levels of reflection and learning. We found that the students had not developed the ability to assess their own teaching or learning, and it made us realise that we need to do more probing for such critical thinking about the way we implement the portfolio task. Portfolios hold much value for summative assessment purposes, but it is important to acknowledge its value to enable assessment for learning. Therefore, a mind shift is needed towards alternative uses of portfolios in teacher education programmes as well as how they can be used for sustainable assessment. The construction of learning portfolios with an explicit focus on learning could bring about important changes for Foundation Phase teacher education students, as it enables them to become more aware of their own learning and growth and could serve as a form of professional development for pre-service teachers that could also serve them well when practising as in-service professionals.